Educational needs for medication safety competence among nurses by clinical ladder stage - Sua Jung; Jinkyung Park (PLoS ONE, 2025)
The objective of this study is to identify the educational needs of nurses in regard to medication safety competence at different career levels. The identification of these needs is grounded in nurse clinical career ladder theoretical frameworks. In April of 2022, focus group interviews were conducted with twenty participants currently engaged in patient care work. These participants were categorized into four groups based on their clinical experience levels: novice (entry to 1 year), advanced novice (from 13 months to 47 months), competent (48 months to 83 months), and proficient (from 84 months). Key educational needs included: self-reflective attitude toward medication safety, effective interaction skills, medication practice knowledge, ability to manage safety risk situations, and establishment of a continuous education system for medication safety. These findings will contribute to the development of medication safety education programs based on a clinical ladder system including attitudes, knowledge, and skills related to self-reflection, self-improvement, and collaboration.